Inhaled aerosol distribution in human airways: a scintigraphy-guided study in a 3D printed model - Verbanck,S; Ghorbaniasl,G; Biddiscombe,MF; Dragojlovic,D; Ricks,N; Lacor,C; Ilsen,B; de,Mey J; Schuermans,D; Underwood,SR; Barnes,PJ; Vincken,W; et al. (Journal of Aerosol Medicine and Pulmonary Drug Delivery, 2016)
Background: While it is generally accepted that inertial impaction will lead to particle loss as aerosol is being carried into the pulmonary airways, most predictive aerosol deposition models adopt the hypothesis that the inhaled particles that remain airborne will distribute according to the gas flow distribution between airways downstream.Methods: Using a 3D printed cast of human airways, we quantified particle deposition and distribution and visualized their inhaled trajectory in the human lung. The human airway cast was exposed to 6 μm monodisperse, radiolabeled aerosol particles at distinct inhaled flow rates and imaged by scintigraphy in two perpendicular planes. In addition, we also imaged the distribution of aerosol beyond the airways into the five lung lobes. The experimental aerosol deposition patterns could be mimicked by computational fluid dynamic (CFD) simulation in the same 3D airway geometry.Results: It was shown that for particles with a diameter of 6 μm inhaled at flows up to 60 L/min, the aerosol distribution over both lungs and the individual five lung lobes roughly followed the corresponding distributions of gas flow. While aerosol deposition was greater in the main bronchi of the left versus right lung, distribution of deposited and suspended particles toward the right lung exceeded that of the left lung. The CFD simulations also predict that for both 3 and 6 μm particles, aerosol distribution between lung units subtending from airways in generation 5 did not match gas distribution between these units and that this effect was driven by inertial impaction.Conclusions: We showed combined imaging experiments and CFD simulations to systematically study aerosol deposition patterns in human airways down to generation 5, where particle deposition could be spatially linked to the airway geometry. As particles are negotiating an increasing number of airways in subsequent branching generations, CFD predicts marked dev